Oxidation of Oven-Dried Cassava Starch Using Hydrogen Peroxide and UV-C Irradiation to Improve Frying Expansion - Iffah Muflihati; Djagal Wiseso Marseno; Yudi Pranoto (Indonesian Association of Food Technologists, 2019)
Native cassava starch usually has low volume expansion. Some modifications were developed to change its physical and chemical characteristic, i.e. hydrogen peroxide addition and UV-C irradiation. The objectives of this study were to determine UV-C intensity, oxidation time, and concentration of hydrogen peroxide addition which resulted in the highest frying expansion of oven-dried cassava starch. Oxidation was conducted with acidification of cassava starch using 1% (w/w) lactic acid, the addition of hydrogen peroxide, and irradiation of UV-C in a tumbler. Combination of UV-C intensity, oxidation time, and hydrogen peroxide concentration were adjusted by Box-Behnken design. Optimization of cassava starch was determined by Response Surface Methodology (RSM), with frying expansion as a main response. Oxidized cassava starch was analyzed for physical and chemical characteristics. The result of this study showed that the oxidation of cassava starch increased the frying expansion, carbonyl and carboxyl content, amylose content, solubility, and decreased the swelling power. The optimum condition of oven-dried cassava starch oxidation was reached at 40 -watt UV-C intensity, oxidation time 2,281 minutes, and hydrogen peroxide concentration 1% (w/w), with the percentage of frying expansion 347,26%.